1988
DOI: 10.1177/00220345880670080101
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Periodontal Health, Salivary Steroids, and Bacteroides intermedius in Males, Pregnant and Non-pregnant Women

Abstract: Relationships between four steroids, determined by radio-immunoassay of whole saliva, and clinical and bacteriological parameters were studied in 90 subjects: males, menstruating females, and pregnant females. Pocket depths and both plaque and gingival bleeding scores were recorded. Total counts and percentages of Gram-negative organisms Bacteroides and B. intermedius were determined from anaerobic cultures of subgingival plaque from 9-14 subjects in each group. None of the clinical parameters for the pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
2
7

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 40 publications
7
62
2
7
Order By: Relevance
“…Studies have shown a high prevalence of P. gingivalis and P. intermedia during the second trimester of pregnancy due to high concentrations of progesterone and/or estradiol, which contribute to bacterial growth. 12,20 Our results corroborate these earlier findings as these species were more frequent during pregnancy at 8 weeks postpartum. Based on accumulated evidence, an increased detection of P. gingivalis during pregnancy and a decrease postpartum were expected.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Studies have shown a high prevalence of P. gingivalis and P. intermedia during the second trimester of pregnancy due to high concentrations of progesterone and/or estradiol, which contribute to bacterial growth. 12,20 Our results corroborate these earlier findings as these species were more frequent during pregnancy at 8 weeks postpartum. Based on accumulated evidence, an increased detection of P. gingivalis during pregnancy and a decrease postpartum were expected.…”
supporting
confidence: 91%
“…12,13,14,15,16,17,18 Various types of analysis and models have proven helpful in understanding the multi-factorial causes of periodontal disease. 7,8,19,20,21 Of these, bacterial challenge studies have provided a valuable contribution to understanding the complex pathogenesis of periodontal disease. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Other investigators also showed no significant microbiological differences between pregnant and non-pregnant women. 5,10 Differences in methods used to assess bacteria may partly explain the results reported. In most cases, the previously mentioned studies 1-3,10,11 used classic microbiological analyses, such as culture methods, which are hampered by the complexity of the periodontal microbiota and the fastidious nature of these microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5]10,11 About 50% of oral bacterial strains cannot be cultured by conventional methods. For some periodontopathogens, molecular techniques, such as PCR, real-time PCR, or DNA-DNA hybridization, have been used successfully to detect microorganisms that are difficult to culture.…”
Section: Introductionmentioning
confidence: 99%
“…The CAL observed in the study sample revealed that loss of periodontal attachment in at least one of the tooth surfaces is frequent. Unlike diabetes mellitus, hormone changes found in pregnancy do not represent an increased risk for the onset and progression of support periodontium destruction 8,13 . Also, to establish the diagnosis of GDM, it has to be shown that carbohydrate metabolism was completely normal before pregnancy 26 .…”
Section: Discussionmentioning
confidence: 99%